Intelligent systems for smart grid : security analysis, optimization, and knowledge discovery - Xu, Yan; Dong, Zhao Yang (Boca Raton : CRC Press, 2018)
Power systems are evolving towards the smart grid paradigm, featuring large-scale integration of renewable energy resources, deeper participation of demand side, and enhanced interaction of electric vehicles to grid. These emerging elements have introduced significant challenges to the system's security, operation, and control, which means that conventional analysis tools are becoming less effective. With a focus on security, optimization, and knowledge discovery, this book presents the cutting-edge intelligent system techniques and their applications to smart grid's real-time stability monitoring and control, operation and planning, and knowledge extraction.
OCLC-licensed vendor bibliographic record.
Keywords: Smart power grids; COMPUTERS / Database Management / Data Mining; SCIENCE / Life Sciences / General; TECHNOLOGY / Electronics / General